Identifying and Eliminating Waste in a Coal Mining Industry: The Value Stream Mapping Analysis - Indriati, Menik Yuni; Rasi, Raja Zuraidah; Setiaji, Bambang; Hadiwinata, Sofian Dwi (International Journal of Sustainable Construction Engineering and Technology, 2023)
Applying Value Stream Mapping (VSM) in the mining industry can increase productivity in production process activities. The coal mining industry has a vital role in life and is an essential investment in the regional economy. However, since 2017, coal production has experienced instability based on data from the Central Bureau of Statistics for East Kalimantan Province (2021) and has yet to meet consumer demand. Previous studies have only shed light on the critical theory that VSM has extended to many industries. However, those studies need to explain the concept of applying VSM to the mining industry. Therefore, to support this theory, a case study from the mining industry was conducted to determine cycle times and identify value-adding and non-value-adding activities. A current state map is developed after making the necessary observations and calculations. Different improvement proposals are identified, and a future state map for the industry is constructed. As a result, a 23.4% reduction in cycle time and 56.1% reduction in lead time ensure its applicability in the mining industry to increase productivity and meet customer demands. VSM is a powerful tool that helps mining managers and operators identify waste and opportunities for improvement. Efficiency is one of the most important things to consider in this industry. This study is especially true in the coal mining sector.